A Critical Evaluation of Glycated Protein Parameters in Advanced Nephropathy: A Matter of Life or Death: A1C remains the gold standard outcome predictor in diabetic dialysis patients - Kalantar-Zadeh, Kamyar (American Diabetes Association, 2012)
Chronic kidney disease remains as one of the major complications for individuals with diabetes and contributes to considerable morbidity. Individuals subjected to dialysis therapy, half of whom are diabetic, experience a mortality of ∼20% per year. Understanding factors related to mortality remains a priority. Outside of dialysis units, A1C is unquestioned as the “gold standard” for glycemic control. In the recent past, however, there is evidence in large cohorts of diabetic dialysis patients that A1C at both the higher and lower levels was associated with mortality. Given the unique conditions associated with the metabolic dysregulation in dialysis patients, there is a critical need to identify accurate assays to monitor glycemic control to relate to cardiovascular endpoints. In this two-part point-counterpoint narrative, Drs. Freedman and Kalantar-Zadeh take opposing views on the utility of A1C in relation to cardiovascular disease and survival and as to consideration of use of other short-term markers in glycemia. In the narrative preceeding this counterpoint, Dr. Freedman suggests that glycated albumin may be the preferred glycemic marker in dialysis subjects. In the counterpoint narrative below, Dr. Kalantar-Zadeh defends the use of A1C as the unquestioned gold standard for glycemic management in dialysis subjects. —William T. Cefalu, MD Editor in Chief, Diabetes Care